PENGARUH AGING PADA KEKUATAN TARIK (TENSILE STRENGTH) FILM LATEKS KARET ALAM BERPENGISI NANOKRISTALIN SELULOSA DAN PENYERASI ALKANOLAMIDA - Marfuah Lubis; Nuim Hayat; Hamidah Harahap (Talenta Publisher (Universitas Sumatera Utara), 2016)
Nanocrystalline cellulose is nano sized filler with high crystallinity and obtanained by hydrolysis of alpha cellulose from sugarcane bagasse. Tensile test of natural rubber latex film filled nanocrystalline cellulose and alkanolamide as compatibilizer after aging treatment have been done. Natural rubber latex films were prepared by coagulant dipping method and followed by vulcanization process at temperature 100 oC and 20 minutes. Aging treatment of natural rubber latex films have done at temperature 70 oC for 24 hours. Tensile test result of natural rubber latex filled nanocrystalline cellulose showed the tensile strength value of aged natural rubber latex film were lower than unaged one. However, tensile strength value of aged natural rubber latex film filled nanocrystalline cellulose modified alkanolamide were higher than unaged film.